What is the relationship between physical activity and cardiovascular risk factors in stroke survivors post completion of rehabilitation? Protocol for a longitudinal study. Issue 11 (15th November 2017) - Fini, Natalie A; Bernhardt, Julie; Holland, Anne E
Abstract : Introduction: Physical activity (PA) can modify cardiovascular and other health risks in people with stroke, but we know little about long-term PA in this group. This study aims to describe PA levels and investigate relationships between PA, cardiovascular risk factors, mobility and participant characteristics (eg, age, mood and fatigue) in the 2 years following rehabilitation discharge after first stroke. Methods and analysis: This is a longitudinal observational study with follow-up at 6, 12 and 24 months after rehabilitation discharge. Inclusion criteria are broad; excluding only those with previous stroke, palliative diagnosis, living more than 2 hours from the centre or admitted less than 5 days. The primary outcome of interest is duration of moderate to vigorous PA (min/day) measured by the Sensewear MF Armband (SWAB). Secondary outcomes include other PA measures measured with the SWAB; cardiovascular risk factors (eg, systolic blood pressure, fasting lipid profile and smoking status), mobility (10 m walk test), the Hospital Anxiety and Depression Scale and the Fatigue Severity Scale. All outcomes, except blood tests, are gathered at each time point. The target sample size is 77. We will explore associations between PA levels, cardiovascular risk factors, mobility and participant characteristics at baseline compared with 6, 12 and 24 months using random-effects regression modelling. The long-term PA of stroke survivors is largely unknown. We hope to identify factors that influence PA and cardiovascular risk in this population, which may help health professionals target the stroke survivors most at risk and implement appropriate treatment, preventative strategies and education. Ethics and dissemination: Approval was granted from Alfred Hospital and La Trobe University Research Ethics Committees. The study results will be disseminated in a number of ways including journal publication and international conference presentations. Trial registration number: ACTRN12613000196741 .